2020
DOI: 10.1530/jme-19-0186
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GLP-1 receptor enhances the chemosensitivity of pancreatic cancer cells

Abstract: This study aimed to determine whether and how the glucagon-like peptide 1 receptor (GLP-1R) agonist liraglutide affects the chemoresistance and chemosensitivity of pancreatic cancer cells to gemcitabine in vitro and in vivo. The GLP-1R and protein kinase A (PKA) levels were compared between the human pancreatic cancer cell line PANC-1 and the gemcitabine-resistant cell line PANC-GR. The in vitro effects of liraglutide on the cell proliferation and apoptosis as well as the nuclear factor-kappa B NF-κB expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…GLP1R (Glucagon Like Peptide 1 Receptor) is a Protein Coding gene which is a member of G protein coupled receptor family. GLP-1R is an important target when treating of type 2 diabetes and obesity [32][33][34]. Recent studies have shown that GLP-1R activation has a cytoreductive effect on human pancreatic cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…GLP1R (Glucagon Like Peptide 1 Receptor) is a Protein Coding gene which is a member of G protein coupled receptor family. GLP-1R is an important target when treating of type 2 diabetes and obesity [32][33][34]. Recent studies have shown that GLP-1R activation has a cytoreductive effect on human pancreatic cancer cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. reported for the first time that liraglutide exhibited significant anti-proliferation and pro-apoptotic effects on gemcitabine-resistant human pancreatic cancer cells resistant to a variety of drugs, by regulating the NF-κB signaling pathway and downstream ATP-binding cassette subfamily G member 2 (ABCG2) ( 213 , 214 ).…”
Section: Effects Of Glucagon Like Peptide-1 Receptor Agonists On Tumor Diseasesmentioning
confidence: 99%
“…Similarly, GLP-1RAs were also demonstrated to exert an inhibitory effect on the growth of breast and cervical cancer, implying the potential application of GLP-1RAs for the treatment of these cancer (10). Zhang et al reported for the first time that liraglutide exhibited significant anti-proliferation and pro-apoptotic effects on gemcitabine-resistant human pancreatic cancer cells resistant to a variety of drugs, by regulating the NF-kB signaling pathway and downstream ATP-binding cassette subfamily G member 2 (ABCG2) (213,214).…”
Section: Effects Of Glucagon Like Peptide-1 Receptor Agonists On Tumor Diseasesmentioning
confidence: 99%
“…For instance, a meta-analysis of randomized, controlled trials involving 63 594 patients with T2D indicated that treatment with albiglutide (a GLP-1 agonist) was associated with a 24% reduction of all sites of cancer when compared to the placebo group [6]. Moreover, in prostate cancer patients, Exendin-4 has been shown to enhance the responsiveness to chemotherapy and reduce cancer growth [7]. In addition to its blood glucoselowering effect, the GLP-1 mimetic exerts an anti-inflammatory effect on a variety of tissues and organs in the body [8].…”
mentioning
confidence: 99%
“…As inflammation plays a key role in the development of many cancer types, it is possible that this understated anti-cancer effect of the GLP-1 mimetic is linked to its anti-inflammatory effect. Of note, the GLP-1 mimetic is reported to inhibit pancreatic and breast cancer cell proliferation through the inhibition of the NF-kB pathway in experimental studies [7,9].…”
mentioning
confidence: 99%